Retrospective Evaluation of Opioid Analgesics Use in Emergency Department: A One-Year Analysis - Tekşen, Yasemin; Kaya, Murtaza (The European Research Journal, 2026)
Objectives: In this study, our aim was to provide data to the literature in terms of both optimal pain control and minimising the side effects of opioids. For this purpose, we retrospectively analysed the opioid model used in the emergency department (ED) of a university hospital. Methods: This is a single-centre, retrospective, and cross-sectional study conducted in the ED of Kütahya Health Sciences University Evliya Çelebi Training and Research Hospital. We retrospectively analysed the electronic medical records of all patients over 18 years of age who were received opioid analgesics in the ED for one year. Data included demographics data (gender, age), diagnosis, type of opioid drug used, hospitalisation and mortality. The study focused on the frequency of opioid use and type of opioid in ED. Results: The study sample included 1392 patients with a mean age of 46.6 years. Of the patients who received opioid analgesics, 45.47% (n=633) were female and 54.53% (n=759) were male. The most common complaint was abdominal pain and 515 patients (37%) received opioids for this reason. The second most common diagnosis was myalgia with 123 patients (8.8%) and the third most common diagnosis was soft tissue injury with 107 patients (7.7%). The most commonly used opioid was fentanyl (n=746, 53.6%). This was followed by tramadol (n=611, 43.9%) and morphine (n=35, 2.5%). Conclusions: Our study found that fentanyl was the most commonly used opioid in the ED, tramadol was preferred for non-traumatic patients such as myalgia, and morphine was rarely used. These results are in line with other data from our country and it has been observed that there is no excessive use of opioids.